Tobat sebagai Landasan Problem Solving: Studi Tafsir Tematik - Iim, Encep; Ismail, Ecep; Syuaib, Ibrahim (Jurnal Riset Agama, 2022)
The main advice of Islam is for sinners to repent immediately because religious arguments explain that repentance is a door of convenience, as well as acting as a procession for eliminating sins. Meanwhile, the problems faced by humans today are increasingly diverse and increasing. This study aimed to discuss repentance as a basis for problem solving. The method used in this study is a qualitative method based on the literature review with the content analysis. Then to explain the verse in this study, it was carried out using the thematic interpretation method (maudhu’i). The result of this study as a discussion that includes the meaning of repentance and the problem solving, verses about repentance related to the problem solving, and the analysis of repentance as a basis for the problem solving. This study concludes that based on the analysis carried out with thematic interpretation steps, it is known that denial and sin cause calamities and problems both on a small and large-scale. Then repentance exists as a purification step for the soul that is offered to eliminate drop calamities and problems and replace them with luck.